2005
DOI: 10.1002/ppul.20161
|View full text |Cite
|
Sign up to set email alerts
|

Do NHLBI lung function criteria apply to children? A cross‐sectional evaluation of childhood asthma at National Jewish Medical and Research Center, 1999–2002

Abstract: Although National Heart Lung Institute (NHLBI) guidelines categorize asthma severity based on spirometry, few studies have evaluated the utility of these spirometric values in grading asthma severity in children. Asthma is thought to be progressive, but little is known about the loss of lung function in childhood. This study sought to determine the spirometric indices in children from 4-18 years of age. Retrospective cross-sectional analysis was performed on all spirometries done in children at the National Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 18 publications
5
55
0
4
Order By: Relevance
“…However, there is insufficient data on the value of parameters of more peripheral airways, such as the forced expiratory flow at 50% of FVC (FEF50%) and/or forced expiratory flow at 25-75% FVC (FEF25-75%), in the monitoring of asthma in children. A large, retrospective cross-sectional analysis of the mean FEV1/FVC ratios from 4-18 years of age demonstrated a steep and consistent decline with increasing age in asthmatic children suggesting the FEV1/FVC ratios provide greater sensitivity in childhood asthma compared with FEV1 [18].…”
Section: Maximal Flow-volume Curvesmentioning
confidence: 99%
“…However, there is insufficient data on the value of parameters of more peripheral airways, such as the forced expiratory flow at 50% of FVC (FEF50%) and/or forced expiratory flow at 25-75% FVC (FEF25-75%), in the monitoring of asthma in children. A large, retrospective cross-sectional analysis of the mean FEV1/FVC ratios from 4-18 years of age demonstrated a steep and consistent decline with increasing age in asthmatic children suggesting the FEV1/FVC ratios provide greater sensitivity in childhood asthma compared with FEV1 [18].…”
Section: Maximal Flow-volume Curvesmentioning
confidence: 99%
“…12,13,[15][16][17] This discord between the clinical presentation and level of lung functionwhich is an important factor in the severity grading -can complicate the assessment of severity, leading to underestimation of disease severity and under-treatment with subsequent poor asthma control. This may contribute to the findings that a substantial number of children with fatal asthma exacerbations had been assessed as having mild disease and were not prescribed regular controller treatment.…”
mentioning
confidence: 99%
“…In the present study, the clinical and spirometry diagnosis of moderate asthma showed total positive correlation (100% [34][35][36] In asthma diffuse narrowing of the airways results in profound physiologic consequences. This narrowing has been thought an occur disproportionately in the small bronchi 37 .…”
Section: Discussionmentioning
confidence: 77%